Effect of Intravenous Ondansetron for Prevention of Spinal Anaesthesia Induced Hypotension during Caesarean Section - Devkota, Kriti; Adhikari, Kiran; Pradhan, Bijay (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Hypotension is one of the most common complications associated with spinal anaesthesia. Maternal hypotension during caesarean section is more dangerous as it can compromise fetal outcome. Serotonin (5-HT3) has been found to induce Bezold Jarisch Reflex (BJR) causing bradycardia and hypotension in background of decreased blood volume. Ondansetron, a serotonin antagonist may play important role in prevention of spinal induced hypotension. The aim of this study is to determine the effect of intravenous ondansetron to prevent spinal induced hypotension during caesarean section. Methods: A prospective randomised double blind study was done among singleton parturients scheduled for elective caesarean delivery under spinal anaesthesia from July 2nd 2020 to October 31st 2021 in College of Medical Sciences Teaching Hospital. One hundred and thirty patients were randomised by lottery method into two groups (group S and group O) each with 65 patients to receive either 4 mg of intravenous (IV) ondansetron diluted in 10 ml of normal saline or 10 ml of normal saline alone. Various haemodynamic parameters like systolic and diastolic blood pressure (SBP/DBP), mean arterial pressure (MAP), heart rate (HR), oxygen saturation (Spo2) and vasopressor requirement were compared between the two groups using SPSS 20. Student’s t test and chi-square test were used for comparison of parametric and non-parametric data. Results: Incidence of hypotension was 28 (43.07%) in saline group and 11 (16.92%) in ondansetron group. There were statistically significant differences in SBP, DBP and MAP at three, six, nine twelve, fifteen and eighteen minutes. Incidence of shivering was 15 (23.07%) in ondansetron while 28 (43.07%) in saline group which was statistically significant. No other benefit of ondansetron was observed in present study. Conclusions: Prophylactic administration of IV ondansetron could significantly reduce the incidence of spinal induced hypotension during caesarean section.